2014
DOI: 10.1093/molbev/msu396
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of the Nonrecombining Regions in the Mating-Type Chromosomes of the Anther-Smut Fungi

Abstract: Dimorphic mating-type chromosomes in fungi are excellent models for understanding the genomic consequences of recombination suppression. Their suppressed recombination and reduced effective population size are expected to limit the efficacy of natural selection, leading to genomic degeneration. Our aim was to identify the sequences of the mating-type chromosomes (a1 and a2) of the anther-smut fungi and to investigate degeneration in their nonrecombining regions. We used the haploid a1 Microbotryum lychnidis-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(103 citation statements)
references
References 82 publications
6
95
2
Order By: Relevance
“…90% of the chromosome length. These genomic data are consistent with previous findings based on marker segregation analyses and optical maps [2628]. This large non-recombining region explains why M .…”
Section: Introductionsupporting
confidence: 92%
“…90% of the chromosome length. These genomic data are consistent with previous findings based on marker segregation analyses and optical maps [2628]. This large non-recombining region explains why M .…”
Section: Introductionsupporting
confidence: 92%
“…Signatures of molecular degeneration associated with recombination suppression have been reported in Neurospora and Microbotryum (Hood et al 2004;Fontanillas et al 2015). There are massive changes in architecture on the Microbotryum mating-type chromosome , a pattern also reported from one of the N. tetrasperma strains (Ellison et al 2011b), and further studies using high quality genomic data have the potential to reveal the commonality of such rearrangements and their link to recombination suppression of fungal mat chromosomes.…”
Section: Discussionmentioning
confidence: 80%
“…Recombination suppression on the chromosome carrying the mating-type locus has evolved independently in several fungal species distantly related to N. tetrasperma, including Podospora, Cryptococcus, and Microbotryum (Fraser and Heitman 2004;Grognet et al 2014;Fontanillas et al 2015) and contributes to our understanding of different aspects of eukaryote genome evolution. Signatures of molecular degeneration associated with recombination suppression have been reported in Neurospora and Microbotryum (Hood et al 2004;Fontanillas et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies addressing MAT gene content and organization in Pucciniomycotina yeasts suggested that mating type-determining regions of these species might encompass a relatively large portion of a chromosome (Coelho et al 2010;Petit et al 2012;Hood et al 2013;Fontanillas et al 2014;Whittle et al 2015). We therefore considered that defining MAT regions in L. scottii would benefit from obtaining genome sequences of two strains of compatible mating types since, unlike the rest of the genome, MAT loci should be clearly distinct in what concerns sequence divergence and gene organization.…”
Section: Resultsmentioning
confidence: 99%